Configurational and conformational analysis of highly oxygenated pyrrolizidines: definitive identification of same naturally occurring 7a-epi-alexines - Wormald, MR; Nash, R; Hrnciar, P; White, J; Molyneux, R; Fleet, G (1998)
The NMR spectra of a number of naturally occurring alexines (tetrahydroxylated pyrrolizidine alkaloids) are analyzed and the consequences of changes in the configuration on the conformation of these bicyclic systems discussed. Unambiguous syntheses of australine (7-epi-alexine) and of 7,7a- epi-alexine have now unequivocally established the structures of two natural products isolated from Castanospermum australe which were insecure due to erroneous NMR data. Chemical shift parameters are unreliable as a method of comparing different samples of identical compounds; however, 1H-1H three bond coupling constants (3J(HH)) provide easy direct comparison between samples and allow assignments of both the relative configurations for the ring protons and the conformation of the pyrrolizidine framework.